Quality of life in women with pelvic floor dysfunction - Mladenović-Segedi Ljiljana; Parezanović-Ilić Katarina; Ćurčić Aleksandar; Višnjevac Nemanja (Vojnosanitetski Pregled, 2011)
Background/Aim. Pelvic floor dysfunction is a frequent problem affecting more than 50% of women in peri- and postmenopause. Considering that ageing and menopause befall in the significant factors causing this issue, as well as the expected longevity of women in the world and in our country, pelvic floor dysfunction prevelence is foreseen to be even higher. The aim of the study was to evaluate impact of the symptoms of pelvic dysfunction on quality of life and examine body image satisfaction in adult women with pelvic organ prolapse presenting to tertiary care clinic for surgical treatment. Methods. This prospective case-control study included 50 patients who presented to tertiary care gynecology clinic for surgical treatment and 50 controls with normal pelvic floor support and without urinary incontinence who presented tertiary care gynecology clinic for other reasons. Both, patients and controls, completed two quastionnaires recommended for the evaluation of symptoms (Pelvic floor distress inventory - short forms) and quality of life impact (Pelvic floor impact questionnaire - short form) of pelvic organ prolapse, and Body Image Scale. Results. The patients scored significantly worse on the prolapse, urinary, colorectal scales and overall score of Pelvic floor distress inventory - 20 than controls subjects (134.91 vs 78.08; p < 0.01). The patients also measured significant decrease in condition- specific quality of life (89.23 vs 3.1; p < 0.01). They were more likely to feel self-conscious (78% vs 42%; p < 0.01), less likely to feel physically attractive (78% vs 22%; p < 0.01), more likely to have difficulty looking at themselves naked (70% vs 42%; p < 0.01), less likely to feel sexually attractive (64% vs 32%; p < 0.01), and less likely to feel feminine (56% vs 16%; p < 0.05), than controls. There were no differencies in their feeling of dissatisfaction with appearance when dressed, avoiding people because of appereance and overall dissatisfaction with their body. There was a positive correlation between decreased quality of life and body image in women with pelvic dysfunction. Conclusion. Women with pelvic floor dysfunction have decreased quality of life and body image.